Resolving disputes in telecommunications global practices and challenges - Prasad, R. U. S. (New Delhi : Oxford University Press, 2011)
This volume not only introduces the concept of dispute resolution, but also stresses the urgent need to revise the various laws in telecommunication. It is composed of eight chapters, each of which addresses a particular topic on dispute resolution and the telecom sector.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Telecommunication -- Law and legislation -- India; Dispute resolution (Law) -- India; Telecommunication -- Law and legislation; Dispute resolution (Law)